Temporal variations in patterns of Escherichia coli strain diversity and antimicrobial resistance in the migrant Egyptian vulture. Issue 1 (1st January 2018) - Sharma, Pradeep; Maherchandani, Sunil; Shringi, B. N.; Kashyap, Sudhir Kumar; Sundar, K. S. Gopi
ABSTRACT: Aims : Multiple antimicrobial resistance in Escherichia coli of wild vertebrates is a global concern with scarce assessments on the subject from developing countries that have high human-wild species interactions. We studied the ecology of E. coli in a wintering population of Egyptian Vultures in India to understand temporal changes in both E. coli strains and patterns of antimicrobial resistance. Methods and Results : We ribotyped E. coli strains and assessed antimicrobial resistance from wintering vultures at a highly synanthropic carcass dump in north-west India. Both E. coli occurence (90.32%) and resistance to multiple antimicrobials (71.43%) were very high. Clear temporal patterns were apparent. Diversity of strains changed and homogenized at the end of the Vultures' wintering period, while the resistance pattern showed significantly difference inter-annually, as well as between arrival and departing individuals within a wintering cycle. Significance of study : The carcass dump environment altered both E. coli strains and multiple antimicrobial resistance in migratory Egyptian Vultures within a season. Long-distance migratory species could therefore disseminate resistant E. coli strains across broad geographical scales rendering regional mitigation strategies to control multiple antimicrobial resistance in bacteria ineffective.